Chronic Aspergillosis in the Guise of Peripheral Lung Neoplasia - N. G. Nikolaeva; T. A. Golimbievskaya; O. V. Shadrivova; E. A. Desyatik; I. A. Bekhtereva; S-A. S. Barmicheva; Yu. V. Borzova; Yu. A. Krivolapov; I. E. Itskovich; N. N. Klimko (Вестник рентгенологии и радиологии)
Two cases of postoperative diagnosis of chronic pulmonary aspergillosis are presented, which were previously regarded as malignant neoplasms. A decisive role in the detection of chronic pulmonary aspergillosis is played by computed tomography, but the diagnosis should be confirmed by laboratory tests. The importance of early diagnosis of chronic pulmonary aspergillosis is associated with high risk of complications during surgery without the use of antifungal drugs.